PENGARUH PERUBAHAN INTENSITAS MATAHARI TERHADAP DAYA KELUARAN PANEL SURYA - Subekti Yuliananda; Gede Sarya; RA Retno Hastijanti (JPM17: Jurnal Pengabdian Masyarakat, 2015)
Fuel oil and coal are formed from fossil utilized as the primary energy source power plants owned by the state electricity company where its presence increasingly depleted. As an energy that can not be renewed will make the higher resale value, so that the necessary studies and research in renewable energy as a source of electrical energy from solar energy one. The use of renewable energy is an alternative to reduce energy demand and optimizing to PLN natural potential. Solar cells are a technology that converts sunlight into electrical energy. The purpose of this study was to determine the relationship of the light intensity output power at a solar cell panel. This research method is the measurement of the intensity of the sun in a real and measuring the output power of solar cell panels that, as for the materials used are lumen meter is used to measure the intensity of sunlight, the multimeter is used for measuring voltage and current, battery charge regulator with a capacity of 10 A, Panel cell with a capacity of 50 Wp solar and battery 65 Ah. Tests conducted for 6 days, each day of testing starting at 6:00 to 18:00. The results showed that the light intensity is highest between the hours of 11:00 to 13:00 with the value of the light intensity of 98,000 lux - 116 200 lux, while the power output of solar cells with a high of 14.80 watts of light intensity measured 116 200 lux.Keywords: solar cells; light intensity; output power; renewable energy